Veriable Models of Physical Education Spesialistsâ€™ Acmeological Competence Formation in the Process of Continious Professional Education - Dereka, Tetiana Grygorivna (Universitas Negeri Semarang, 2018)
Objectives; testing the variability of physical education specialistsâ€™ continuous professional training models aimed at the acmeological competence formation in the experimental way. Methods; the study involved students of the â€œPhysical Educationâ€ specialty (n = 194). Selection and modification procedures were applied to the following experiment methods, such as the â€œStudentsâ€™ learning motivationâ€ revealing method (A. A. Rean, V. A. Yakunin); the â€œPersonality maturityâ€ questionnaire; the â€œEmotional intelligenceâ€ revealing test (N. Hall); the â€œEvaluation of aspirations levelâ€ questionnaire used for the integral motivation activity estimation index; the â€œorganizational capabilities assessing methodsâ€; the â€œCommunication skills revealingâ€ method; the â€œPersonalityâ€™s creative potential self-esteemâ€ method. Results; The structure of the physical education specialistsâ€™ acmeological competence was identified. The acmeological competence components including acme-motivational, cognitive-acmeological, acmeological-activity and acme-traits of specialistâ€™s personality ones have been characterized. The models of physical education speciallistsâ€™ continuous professional training, such as the professional motivation predominanting; practically-focused; and sports-activity focused ones were distinguished on the acmeology basis. The forming of physical education specialistsâ€™ acmeological competence components according to the variable continuous training models has been investigated experimentally. The study revealed a high correlations between the acmeological competence formation level and the characterized components. Conclusions; summarizing the study of acmeologically aimed physical education specialistsâ€™ continuous professional training the following statements were revealed: the model with the professional motivation predominanting is carachterised by the high level of acme motivational component formation; the practically-focused model is characterized by the high level of cognitive acmeological component formation; the sports-activity pattern is characterized by the high level of bouth acmeological-activity and acme-traits of specialistâ€™s personality components.